2022
DOI: 10.1007/s10639-021-10800-z
|View full text |Cite
|
Sign up to set email alerts
|

How to improve the design of experimental studies in computing education: Evidence from the international assessments

Abstract: Cluster randomized trials are frequently used in educational research for methodological reasons. This study aims to improve the efficiency of cluster randomized trials on computer/information literacy and computational thinking. The study employs a two-level hierarchical linear model to estimate (i) intraclass correlation coefficients, (ii) the amount of explained variances given selected predictors, and (iii) minimum detectable effect sizes given the set of plausible scenarios. Two data cycles from the Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that college ICT support has a direct impact on the development of students’ self-efficacy (Guo et al, 2022; Q. Wang & Zhao, 2021; Yildiz et al, 2022). Tondeur et al (2018) emphasized that students use of strategies (e.g., collaboration, authentic technology experiences, and curriculum feedback) is reflected in their awareness through an increased sense of ICT self-efficacy during learning.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Numerous studies have shown that college ICT support has a direct impact on the development of students’ self-efficacy (Guo et al, 2022; Q. Wang & Zhao, 2021; Yildiz et al, 2022). Tondeur et al (2018) emphasized that students use of strategies (e.g., collaboration, authentic technology experiences, and curriculum feedback) is reflected in their awareness through an increased sense of ICT self-efficacy during learning.…”
Section: Research Hypothesesmentioning
confidence: 99%